The effectiveness of HIV/AIDS education models for adolescents with speech disabilities - Dedes Fitria; Sri Wahyuni; Elin Supliyani; Fauzia Djamilus; Ari Kurniarum; Sri Sumarni (PAGEPress Publications, 2024)
Adolescents with disabilities deserve the best health care without discrimination. They can access gender-sensitive health care and rehabilitation. Health services include promotive, preventive, curative, and rehabilitative care. HIV and AIDS prevention in disabled people must start as soon as possible. Those with speech disabilities are encouraged to reach their full independence potential in case of an incident. This study tested an HIV/AIDS education model for speech-impaired people. At Indonesia's School of Disability, a non-randomized control group pre- and post-test design was used. In the study, 60 speech-impaired students were divided into 30 intervention and 30 control groups. Analyses used T-tests. Speech-disabled people's knowledge and attitudes improved with the virtual HIV/AIDS education model (P=0.007). Therefore, the HIV/AIDS education model should be implemented using virtual platforms to improve knowledge and attitudes, especially among speech-disabled teens. Virtual reproductive health education for children with speech disabilities improves knowledge and attitudes more than traditional methods, especially among visually impaired children.